Economic Rights of Women Under Sokoto Caliphate: A Lesson for Contemporary Women in Nigeria - Murtala Hanafi; Yusha'u Hanafi Jibril (Demak Universal Journal of Islam and Sharia, 2024)
This paper economic rights of women under the Sokoto Caliphate, a lesson for women of contemporary Nigeria, discusses the various economic activities in which women engaged themselves in Sokoto without interference from the men. The rights of women have occupied a prominent place in the scheme of Islamic affairs from the inception of the Islamic message. It is no longer history to state that the Prophet SAW upgraded the status of women from what it used to be and made them equal to the male gender throughout his Prophethood. Part of the rights accorded women in the early days of Islam includes economic rights. This paper highlights some of the entrepreneurship which women engaged in and also the challenges which they faced in the caliphate before now. It also discussed the rights enjoyed by Muslim women in Sokoto. Adequate attention is devoted to the proprietary and employment rights of women in Sokoto as well as other such challenges affecting the enjoyment of rights accorded Muslim, women in Islam to cater for their economic well-being. The paper is structured into major parts starting with the proprietary right of women in Islam contemporary to the economic rights of women in Nigeria. As a lesson and challenge to the contemporary women in Nigeria. The study adopted a qualitative research method where secondary sources of data were utilised and analysed as its methods of analysis.